2007
DOI: 10.1111/j.1745-9125.2007.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

POLICING, DRUGS, AND THE HOMICIDE DECLINE IN NEW YORK CITY IN THE 1990s*

Abstract: This research reassesses the role of policing and drugs in the sharp homicide decline in New York City in the 1990s. Drawing on theoretical arguments about “broken windows” policing and lethal violence associated with the diffusion of crack cocaine, we estimate the effects of measures of misdemeanor arrests and cocaine prevalence on homicide rates with pooled, cross‐sectional time‐series data for 74 New York City precincts over the 1990–1999 period. The results of mixed regression models reveal a significant n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 31 publications
0
77
2
3
Order By: Relevance
“…Another study analyzed data from NYC from 1988-2001 and found that while ordermaintenance policing did have significant impacts on robbery and homicide rates, the reductions were relatively modest (Rosenfeld, Fornango, & Rengifo, 2007). Yet another study of NYC's use of ordermaintenance policing in the 1990s found the tactic had a significant effect on gun-related homicide, but not for murders not involving a firearm (Messner et al, 2007). In addition to this mixed empirical evidence, other scholars have argued that the crime decline in NYC during the 1990s simply mirrored national trends and was likely a sign of such factors as the decline of the crack cocaine epidemic rather than any policing efforts (Eck & Maguire, 2000).…”
Section: Broken Windows Policingmentioning
confidence: 92%
“…Another study analyzed data from NYC from 1988-2001 and found that while ordermaintenance policing did have significant impacts on robbery and homicide rates, the reductions were relatively modest (Rosenfeld, Fornango, & Rengifo, 2007). Yet another study of NYC's use of ordermaintenance policing in the 1990s found the tactic had a significant effect on gun-related homicide, but not for murders not involving a firearm (Messner et al, 2007). In addition to this mixed empirical evidence, other scholars have argued that the crime decline in NYC during the 1990s simply mirrored national trends and was likely a sign of such factors as the decline of the crack cocaine epidemic rather than any policing efforts (Eck & Maguire, 2000).…”
Section: Broken Windows Policingmentioning
confidence: 92%
“…Several studies indicate that U.S. cities that experienced high levels of crack activity or significant increases in crack use in the 1980s also experienced momentous upsurges in violent crime (Baumer et al, 1998;Messner et al, 2005;Messner et al, 2007). However, other studies find less definitive support.…”
Section: The Rise and Fall Of The Crack-cocaine Marketmentioning
confidence: 94%
“…Research examining more targeted police initiatives has provided some support for their contribution to falling crime rates, such as Boston's Operation Ceasefire (Braga et al, 1999), New York City's Compstat (Messner et al, 2007), Richmond's Project Exile (Raphael and Ludwig, 2003), Kansas City's Gun Experiment and St. Louis' Firearm Suppression Program (Rosenfeld and Decker, 1996). Rosenfeld et al, (2005) compared police strategies and their effectiveness in reducing violent crime trends among the programs in Boston, New York City, and Richmond along with a sample of cities that did not implement these police tactics.…”
Section: Police Force and Policing Strategiesmentioning
confidence: 98%
“…Na literatura internacional, há diferentes vertentes explicativas para os possíveis determinantes na redução de taxas de homicídio: aquelas que privilegiam ações na área de segurança pública, especialmente as alterações na atuação policial (Cerda et al, 2009;Messner et al, 2007), o aumento no contingente policial (Levitt, 2004), as políticas de encarceramento (Levitt, 2004;McCall;Parker;MacDonald, 2008) e de desarmamento (Blumstein;Rivara;Rosenfeld, 2000); outras que indicam mutações na dinâmica do mercado ilegal de drogas (Blumstein;Rivara;Rosenfeld, 2000;Levitt, 2004;Messner et al, 2007); as que destacam alterações na composição demográfica da população, inclusive a diminuição do número de jovens (Phillips, 2006); ou, ainda, as correntes que apontam melhorias na qualidade de vida e maior coesão social (LaFree, 1999).…”
Section: Introductionunclassified